ENSO Bimodality and Extremes. Issue 9 (3rd May 2019) - Rodrigues, Regina R.; Subramanian, Aneesh; Zanna, Laure; Berner, Judith
Abstract: Tropical sea surface temperature (SST) and winds vary on a wide range of timescales and have a substantial impact on weather and climate across the globe. Here we study the variability of SST and zonal wind during El Niño‐Southern Oscillation (ENSO) between 1982 and 2014. We focus on changes in extreme statistics using higher‐order moments of SST and zonal winds. We find that ENSO characteristics exhibit bimodal distributions and fat tails with extreme warm and cold temperatures in 1982–1999, but not during 2000–2014. The changes in the distributions coincide with changes in the intensity of ENSO events and the phase of the Interdecadal Pacific Oscillation. We also find that the strongest Easterly Wind Bursts occur during extreme El Niños and not during La Niñas. Maps of SST kurtosis can serve as a diagnostic for the thermocline feedback mechanism responsible for the differences in ENSO diversity between the two periods. Plain Language Summary: El Niño and La Niña in the Tropical Pacific Ocean affect weather, water resources, and fragile ecosystems around the globe. These phenomena have been extensively studied, yet we know relatively little on how and why El Niño and La Niña have changed over the past several decades. We use observational data sets of the ocean temperature and atmospheric winds to quantify and understand the nature of the change in these phenomena. We show that extreme El Niño and La Niña events occur more often in the 1980s and 1990s while in the past two decades there have been fewer extreme events in the Tropical Pacific. We also find that the strongest easterly wind anomalies occur during the extreme El Niño years only, which can then change how the atmosphere and ocean interact during these events compared to more moderate warm events. The Interdecadal Pacific Oscillation appears to modulate the decadal changes in the extremes of these events. Key Points: The historical record shows large changes in higher‐order moments of ENSO variability Strong bimodality in El Niño SST is linked to westerly wind bursts Strongest easterly wind bursts occur during the extreme El Niño, not La Niña, years